Reshaping Multiculturalism through Constitutions and Receptivity in Nepal (Sudurpaschim Spectrum, 2026)
Being a diverse and multicultural country, Nepal is characterized by a wide range of components such as languages, cultures, ethnicities, and religions. While the Constitution 2015 is more liberal and inclusive than previous constitutions, the state has numerous obstacles to overcome in order to accommodate dissatisfied voices and maintain harmony among different entities. Discrimination, economic disparities, language barriers, and insufficient representation of marginalized groups persist, hindering the full realization of multiculturalism. The paper explores these challenges and stresses the importance of respecting cultural differences and promoting inclusivity. In addition, it also acknowledges some positive initiatives, such as increased political representation of women and marginalized groups and a growing awareness of the need to address discrimination in areas like inter-caste marriages. The article also advocates a more inclusive democratic system, dialogue among various indigenous communities and the dissemination of non-academic knowledge to build a fairer, more harmonious society.